Mental representation and learning in complex action: a perceptual-cognitive view on mental and physical practice - Frank, C. (Universität Bielefeld, 2014)
An extraordinary and extremely sophisticated capability of human beings is that of performing motor actions in a goal-directed manner. Consider, for example, skilled golfers proficiently performing golf putts under various constraints such as putts from various distances, putts on different greens, or putts comprising diverse breaks. How did they arrive at performing in such a sophisticated, adaptive and yet stable, manner? The two most common means to learn a motor action are through physical and mental practice. Both types of practice have shown to lead to performance improvements, and in this sense, to promote motor learning. However, motor learning as induced by mental and physical practice has rarely been approached with a specific focus on the perceptual-cognitive, representational level of action organization. To date, research has yet to systematically investigate the influence that mental and physical practice have on the motor action system in terms of the development of mental representation of complex action. The present work seeks to bridge this particular research gap. Specifically, motor learning and the influence of two types of practice, mental practice (i.e., covert practice) and physical practice (i.e., overt practice), are approached from a perceptual-cognitive, architecture based point of view. As such, the present work provides insights into the perceptual-cognitive adaptations that occur within the motor action system during early skill acquisition. In short, the theoretical contributions of the present work entail elaborations on the distinct influence of mental and physical practice on the motor action system, and the level of mental representation in particular, drawing back on the cognitive action architecture approach. From an empirical standpoint, three learning studies are described that shed further light on motor learning and mental practice from a perceptual-cognitive, representation-based point of view. Chapter 1 provides an overview of the theoretical perspectives and empirical evidence relating to motor learning and mental practice, with a particular focus on perceptual-cognitive approaches and the functional role of mental representation. Accordingly, the cognitive action architecture approach is described and the potential influence of mental and physical practice within the levels of action organization is sketched, followed by an outline of the purpose of the present work. Chapter 2 explores the development of one`s mental representation of a complex action during motor learning. In the study presented, the question was examined whether the mental representation structure of a complex action changes over the course of practice, and whether this change reflects a development toward a more elaborate and functional structure, such as that of an expert. Together with improvements in putting performance, mental representations of the putt were found to change with practice, developing toward more functional ones. Specifically, mental representation structures of the practice group became more similar to a golf expert structure over the course of practice, reflecting distinct phases of the putting movement (i.e., preparation, forward swing, and impact). Instead, mental representation structures of the (no practice) control group did not change and remained dissimilar in comparison to an expert structure. Thus, this study shows that, along with improvements in (overt) performance, the (covert) mental representation of a complex action develops as a result of practice. Chapter 3 provides further insights into the development of one`s mental representation of a complex action according to type of practice, with a particular emphasis on mental practice. Accordingly, the question was investigated whether mental representation structure of a complex action changes as a result of both mental and physical practice as well as a combination of both, and whether the changes reflect a development toward a more elaborate and functional structure. In line with findings from study one, mental representations of the putt developed over the course of practice. Interestingly, mental practice, either solely or in combination with physical practice, led to even more elaborate representations compared to physical practice alone. Specifically, mental representation structures of the groups practicing mentally became more similar to a functional structure, thereby reflecting well the functional phases of the putting movement, whereas those of the physical practice group revealed less development toward a functional structure. Furthermore, putting performance improved over the course of practice, reflecting the well-known pattern of magnitude of improvement according to type of practice. Specifically, combined mental and physical practice was most effective, followed by physical practice, mental practice and no practice (i.e., combined practice > physical practice > mental practice > no practice). Statistically, the combined practice group proved more effective than mental practice only and no practice with respect to performance. Hence, findings from the first study were replicated such that, along with improvements in performance, mental representation of a complex action develops as a result of practice. More importantly, however, according to the results of the second study, mental practice added to the development leading to even more elaborate representations. Notably, these (covert) changes do not seem to transfer one-to-one to the (overt) motor output. Chapter 4 further explores the perceptual-cognitive background of performance changes that occur within the motor action system as a result of mental and physical practice, thereby providing insights into both mental representations and gaze behavior during complex action. Accordingly, the question was investigated whether mental representation structure of the putt and gaze behavior during putting changes with both physical and combined mental and physical practice, and whether the changes reflect a functional development. Similar to findings of study two, combined mental and physical practice led to more developed representation structures of the putt compared to physical practice alone. As an extension, combined practice as well led to more elaborate gaze behavior prior to execution of the putt. Specifically, final fixations prior to the onset of the putting movement were longer after practice for the group practicing mentally in addition to physical practice in comparison to the control group. This was not the case for the group practicing physically only. Instead, putting performance improved similarly in both practice groups over the course of practice. Thus, the results of study three once more indicate that it is the mental component of the practice that leads to more developed representation structures and more functional gaze behavior. However, similar to study two, these (covert) changes do not become evident on (overt) motor output. Chapter 5 summarizes the key findings of the three learning studies and discusses them with recourse to the cognitive action architecture approach to motor learning and mental practice. In particular, based on the findings of the present work, the differential influence of mental and physical practice on action organization within the motor action system is discussed, followed by an outline of both limitations and prospects for future research. Altogether, this body of work clearly demonstrates that motor learning by mental and physical practice is associated with perceptual-cognitive adaptations within the motor action system and with functional changes in mental representation structures of complex action in particular, and it furthermore indicates that mental and physical practice differ in their influence on the different levels of action organization.